Consumer Perception of Food Safety and Valuation of Statistical Life: A Contingent Valuation Study - Bingjie Liu; Yinuo Na; Yi Li; Dan Wang; Xin Zhang (Foods, 2024)
The value of statistical life (VSL) reflects the trade-off between money and the risk of death. It is a key indicator for conducting regulatory impact assessments. The main purpose of this study was to estimate the VSL in the field of food safety. At the same time, it investigates respondents’ willingness to pay (WTP) for reducing the risk of death from foodborne illnesses and explores the impact of factors such as the average household monthly income, health status, and education level on WTP. We conducted a survey using an open-ended contingent valuation method among 1307 respondents aged 18 and above to determine their WTP. Based on the WTP survey results, we calculated the VSL in the food safety sector. We used binary logit and Tobit models to analyze the influencing factors. The results of the study show that the median WTP for reducing the risk of foodborne illness is CNY 100 (USD 16), and the estimated VSL is approximately CNY 9.09 million (USD 141 million). Indicators such as the average household monthly income, health status, and education level are important factors affecting WTP. This study will help practitioners, researchers, and policymakers understand the current population’s attitudes towards food safety regulations and determine the priorities for regulatory implementation. Future research can explore the effects of different elicitation methods, cultural differences, and regional variations on WTP and VSL.